Effect of La on Magnetic Properties of BaFe12O19. Issue 4 (2nd October 2017) - Shekhawat, D.; Verma, S.; Sharma, P.
ABSTRACT: Among the M-type hexaferrites, barium ferrites (BaFe12 O19 ) have greatest technology interest due to its low cost and moderate magnetic properties. Magnetic properties can be tailored by changing processing condition and by suitable cationic substitution at Ba or Fe site. Lanthanum substituted (Ba1–x Lax Fe12 O19 ) and extra addition of lanthanum (BaFe12 O19 (Lax )) in barium hexaferrite are successfully prepared by solid state synthesis method. The structural, magnetic and microstructural characterizations are studied by X-ray diffractometer (XRD), mössbauer spectroscopy, vibrating sample magnetometer and scanning electron microscope (SEM), respectively. XRD patterns show single phase BaFe12 O19 for La-substituted samples, whereas a secondary phase of barium mono-ferrite (BaFe2 O4 ) is also detected for La-extra addition samples. Crystallite size is found to increase with La substitution. SEM shows the surface morphology of La-substitution and La-extra addition BaFe12 O19 . The magnetic properties show the variation in coercivity ( Hc ) and saturation magnetization ( Ms ) with La substitution and extra addition. Coercivity is found to decrease abruptly in La-extra addition samples, however, no such variation is observed for La-substituted samples. Ms is found to decrease for La-substituted barium hexaferrite, whereas Ms for La-extra addition samples first decreases and then increases to maximum value. GRAPHICAL ABSTRACT: